Methods of contraception for men - Anna Małgorzata Łopuszyńska; Mateusz Pawlicki; Ewa Piekarska; Magdalena Kozioł; Aleksandra Krasa; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
Many pregnancies in the world are unintentional and some of them end in abortion, hence there is a great need and amount of research on contraceptives. There are many methods of pregnancy prevention for women. However, men also want to be responsible for their reproductive health. Currently, there are few methods of contraception for men (male condoms, vasectomy, withdrawal) and they have their drawbacks, so research on new contraceptives for men is ongoing. Hormonal methods under research include testosterone, nestorone, and DMAU. On the other hand, adjudin, WIN 18.446, BMS-189453 and RISUG are promising methods of non-hormonal male contraception. These substances can be a discovery and a breakthrough in male contraception, they will allow men to better control their fertility and reproductive health, and can also be a suitable solution for couples in which there are contraindications for women to use contraception.